Implementasi motion grafis video animasi 2D untuk pengenalan seni, budaya, dan kuliner khas di Provinsi Kalimantan Barat - Prasetya, Irwan Adhi; Ramadhan, Iwan (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The growing development of information technology cannot be separated from the use of Multimedia as a means of supporting the delivery of information. Information about West Kalimantan Province is needed by the community in the world of education and knowledge because West Kalimantan has a variety of cultures. This diversity exists because the social life, customs, and art of the region are different from one another. This cultural diversity is a wealth and can be seen in house models, traditional dances, folk songs, musical instruments, and culinary specialties of each Regency / City in West Kalimantan. Therefore, the purpose of this research is to expand knowledge by creating a Motion Graphic 2D Animation Video as an introductory media about the arts, culture, and culinary specialties of West Kalimantan province which is easy to understand and learn and provide information in an interesting way. The research method used is Multimedia Development Life Cycle (MDLC). The development of this multimedia method is carried out based on six stages, namely concept, design, material collecting, assembly, testing, and distribution. These six stages do not have to be sequential in practice, they can be interchanged. However, the concept stage must be the first thing done. The Research Hypothesis is that Information Delivery using this media makes users interested in using it and is easy to use. makes users interested in using it and easy to understand in the process of conveying information.